China’s Social Credit System: A Challenge to Human Rights - Nguyen, Van Quan; Lafrance, Sébastien; Vu, Thanh Cu (Law, State and Telecommunications Review, 2023)
[Purpose] To examine the origin and evolution of China’s social credit system. [Methodology/Approach/Design] A doctrinal approach is employed with secondary sources. [Findings] China’s social credit system has some adverse effects on the fundamental principles of international human rights law.